Grammatical Accuracy in Graph Description Among EFL Learners - Dini Riandini (Pusat riset dan Inovasi Nasional, 2026)
The ability to describe graphs accurately in English is an essential academic skill for EFL learners, particularly in higher education contexts where students are required to interpret and communicate visual data. However, many learners still experience difficulties in producing grammatically accurate graph descriptions. This study aims to investigate the level of grammatical accuracy demonstrated by EFL learners in graph description tasks and identify the grammatical aspects that require further improvement. Employing a descriptive qualitative approach, the research analyzed 30 samples of students’ written graph descriptions produced by undergraduate learners. The analysis focused on several grammatical aspects, including subject–verb agreement, tense consistency, article usage, sentence structure, prepositions, and punctuation. The findings reveal that students frequently struggle with subject–verb agreement and article usage, while punctuation errors occurred less frequently. The study highlights that grammatical accuracy remains an important challenge for EFL learners in academic writing tasks involving data interpretation. Therefore, it is recommended that grammar instruction be integrated more intensively into graph description activities in English classes. The findings are expected to contribute to the development of more effective teaching strategies in academic writing instruction for EFL learners.